Breakup and interaction of immiscible liquid jets - Parmar, Harisinh (Curtin University, 2014)
This work investigates the effects of multiple jet interactions and jet instability on droplet production and breakup using experimental and computational techniques. Experiments and CFD simulations of water in oil have been performed to understand mechanism of jet interactions and instability for single and multiple jets. The new insights provide an important basis to manipulate multiple jets, which produce better emulsion than single jet in micro channel reactors.